Administration of recombinant human thrombopoietin is associated with alleviated thrombocytopenia in adult intensive care unit patients with pneumonia: A single-center retrospective study - Chen, Bailiang; Xuan, Jiabin; Wu, Feng; Shi, Nengxian; Dai, Jianwei; Cai, Shumin; An, Shengli; Huang, Qiaobing; Huang, Xiaoling; Chen, Zhongqing; Zeng, Zhenhua (Frontiers in Pharmacology, 2022)
Background: Recombinant human thrombopoietin (rhTPO) is reported to stimulate platelet production and increase peripheral platelet counts; it is primarily used to manage chemotherapy-induced thrombocytopenia and idiopathic thrombocytopenic purpura. However, the effect of rhTPO in patients with pneumonia and thrombocytopenia remains uncertain. Objective: To assess the association of rhTPO and platelet counts in ICU patients with pneumonia and thrombocytopenia. Materials and Methods: A retrospective cohort study was performed in the ICU department, Nanfang Hospital, Southern Medical University, Guangzhou, China. From January 2016 and April 2021, patients with pneumonia and thrombocytopenia were allocated to two groups—the rhTPO and no-rhTPO groups—according to whether they received rhTPO treatment or not during their ICU stay. Demographical and clinical data were collected and analyzed using statistical software; p<0.05 was considered statistically significant. Results: Out of 327 patients, 149 were in the rhTPO group and 178 were in the no-rhTPO group. Within the first seven days, platelet counts increased more for patients in the rhTPO group compared with those in the no-rhTPO group (99.21±102.613 vs 2.08±43.877, p=0.000). The clinical recovery rate of platelets increased within seven days (65.8% vs 18.5%, p=0.000) and, after seven days of enrollment, hemorrhagic scores decreased more apparently in the rhTPO group (2.81 ± 2.856 vs 1.16 ± 2.123, p=0.000). Further, bleeding events ceased in 66.7% of the patients in the rhTPO group compared with 37.3% of the patients in the no-rhTPO group (p=0.000). Less red-blood-cells transfusions were needed in the rhTPO group (3.639±4.630 vs 5.818±6.858, p=0.009). Furthermore, through logistic regression, rhTPO administration was found to be an independent indicator that affected the platelet recovery rate within seven days. Conclusions: This study finds that rhTPO administration is associated with increased platelet counts, alleviated bleeding, and reduced blood transfusion. For patients with pneumonia and thrombocytopenia, rhTPO may be an effective therapeutic drug; however, more RCT trails are needed to confirm our observation.